Boundedness and Compactness of Specific Weighted Composition Operators on the Zygmund-Orlicz Space. (2nd June 2022) - Zhou, Hang
Abstract : We say φ ∈ U if a constant C φ > 1 could be found, such that φ s t ≤ C φ s φ t, s > 1, t > 0 . Under the assumption φ ∈ U, boundedness and compactness of weighted composition operators on the Zygmund-Orlicz space Z φ are investigated in this paper.